2008
DOI: 10.1111/j.1750-3841.2008.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trans Fatty Acids Content in Popular Western‐Style Products in China

Abstract: To date, the published information on trans fatty acids (TFAs) in food products in China remains scarce and of questionable accuracy. Systematic approaches to educate the consumers and to ensure proper labeling of TFAs are among the many urgent challenges the regulatory agencies in this rapidly growing country have to face. In the present study, 97 most popular, national brand food products on the Chinese market, including 6 cheeses, 10 chocolates, 10 crisps, chips, and fries, 10 ice creams, 15 margarines, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
5
16
5
Order By: Relevance
“…They stated that the use of average values for theTFAs content in a food category was of a limited value. Fu et al (2008) investigated TFAs in nationalbrand western-style products including 10 chocolate samples in China. The authors determined the average contents of TFAs as 0.80%, 0.57%, and 1.87% of total fatty acids in chocolate with nuts, dark chocolate, and milk chocolate, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They stated that the use of average values for theTFAs content in a food category was of a limited value. Fu et al (2008) investigated TFAs in nationalbrand western-style products including 10 chocolate samples in China. The authors determined the average contents of TFAs as 0.80%, 0.57%, and 1.87% of total fatty acids in chocolate with nuts, dark chocolate, and milk chocolate, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…0?5 % of fat content) was found in 80 % and 33 % of the Western-and Chinesestyle food products, respectively. However, none of the ninety-seven products were labelled for TFA (12) . Owing to their adverse effect on health, saturated fat and TFA have drawn more attention than other nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The Beijing survey was the only study that we have identified in our literature search that provided related detailed information. Another study (12) examined only the labelling of TFA-related information. Shanghai and Beijing are the two largest cities in China.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating this type of fat significantly improves the consistency, sensory characteristics and stability of these products [2,3,4]. It is estimated that 90% of the trans fat present in the Western diet is derived from the hydrogenation process [5].…”
Section: Introductionmentioning
confidence: 99%